2006
DOI: 10.1002/jnr.20860
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia impairs performance of adult mice in the two‐way shuttle box but not in the Morris water maze

Abstract: We have previously found that neonatal intermittent hypobaric hypoxia exposure enhanced mouse spatial, but impaired associative, cognition. This study sought to investigate the effects of hypobaric hypoxia on adult mice cognition. Mice were exposed to 2, 5, 10, 15, or 25 days of intermittent hypoxia (IH; 4 hr/day) at 2 km (16.0% O2) or 5 km (10.8% O2) altitudes in a hypobaric chamber for the Morris water maze (MWM) test and exposed to IH for 2, 10, or 25 days for the shuttle-box test. Amino acid dynamics in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
(66 reference statements)
3
8
1
Order By: Relevance
“…Consistent with previous studies of IH (44,53) and patients with OSA (20, 37), we observed impaired learning and memory. The effects of IH and sleep deprivation were previously determined to have distinct effects on the central nervous system, although both have separately been associated with impaired memory function, specifically in spatial learning tasks (25)(26)(27).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous studies of IH (44,53) and patients with OSA (20, 37), we observed impaired learning and memory. The effects of IH and sleep deprivation were previously determined to have distinct effects on the central nervous system, although both have separately been associated with impaired memory function, specifically in spatial learning tasks (25)(26)(27).…”
Section: Discussionsupporting
confidence: 93%
“…The effects of IH and sleep deprivation were previously determined to have distinct effects on the central nervous system, although both have separately been associated with impaired memory function, specifically in spatial learning tasks (25)(26)(27). It was also reported that 3 days of IH exposure prior to acquisition decreased consolidation, consistent with other findings of IH impairing learning and memory after sustained exposure (48,53). Differences in learning and memory were only observed in the passive avoidance task.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…To our knowledge, our study is the first reporting that acute and repeated hypoxic exposure enhances performance of adult mice in a water maze. In contrast with our results, other results suggest that hypoxic exposure impairs, or does not affect, the ability of learning and memory in adult and neonatal animals [8,9,32] . This discrepancy could be explained by the differences in the methods for hypoxic exposure and differences in the development stage in which animals were exposed to hypoxia.…”
Section: Discussioncontrasting
confidence: 56%
“…Compared with the control group, the spatial cognitive ability of mice exposed to hypoxia once was not changed. Zhang et al [24,32] have reported that intermittent hypoxia could enhance spatial cognitive ability in young mice but did not affect this ability in adult mice. Others also reported that brief hypobaric hypoxia enhanced animals' cognition.…”
Section: Discussionmentioning
confidence: 99%